Light Propagation in Gain Media : Optical Amplifiers / [electronic resource] - Premaratne, Malin; Agrawal, Govind P. (Cambridge : Cambridge University Press, 2011)
Over the past two decades, optical amplifiers have become of key importance in modern communications. In addition to this, the technology has applications in cutting-edge research such as biophotonics and lab-on-a-chip devices. This book provides a comprehensive treatment of the fundamental concepts, theory and analytical techniques behind the modern optical amplifier technology. The book covers all major optical amplification schemes in conventional materials, including the Raman and parametric gain processes. The final chapter is devoted to optical gain in metamaterials, a topic that has been attracting considerable attention in recent years. The authors emphasize analytical insights to give a deeper, more intuitive understanding of various amplification schemes. The book assumes background knowledge of electrical engineering or applied physics, including exposure to electrodynamics and wave motion, and is ideal for graduate students and researchers in physics, optics, bio-optics and communications.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Optical amplifiers